2006
DOI: 10.1677/joe.1.06779
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-replacement therapy depresses the ex vivo production of inflammatory cytokines by circulating antigen-presenting cells in aging type-2 diabetic men with partial androgen deficiency

Abstract: Androgens are considered to have immunomodulatory effects but their cellular mechanisms of action remain largely unknown. In the present study we prospectively analyzed the serial effects of androgen-replacement therapy on both the distribution of peripheral blood lymphocytes, monocytes and dendritic cells as well as on the production of interleukin (IL)-1 , IL-6 and tumor necrosis factor (TNF ) inflammatory cytokines by circulating monocytes and CD33 myeloid, CD16 and plasmacytoid dendritic cell subsets, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 54 publications
3
73
0
4
Order By: Relevance
“…The preventative effect of androgens on FR demonstrated that their direct bronchorelaxing response is nongenomically mediated in ASM (Kouloumenta et al 2006, Bordallo et al 2008, Espinoza et al 2013. The ability of androgens to abolish the DR indicates their immunomodulating, and antiinflammatory genomically mediated effect (Cutolo 1997, Dalal et al 1997, Malkin et al 2004, Corrales et al 2006, Traish et al 2011, Koziol-White et al 2012. This protective activity of androgens against a bronchospasm revealed the same order of potency as that observed in the in vitro experiments described below (5b-DHT exhibited major potency than TES and 5a-DHT).…”
Section: Bronchospasm Prevention By Androgensmentioning
confidence: 72%
“…The preventative effect of androgens on FR demonstrated that their direct bronchorelaxing response is nongenomically mediated in ASM (Kouloumenta et al 2006, Bordallo et al 2008, Espinoza et al 2013. The ability of androgens to abolish the DR indicates their immunomodulating, and antiinflammatory genomically mediated effect (Cutolo 1997, Dalal et al 1997, Malkin et al 2004, Corrales et al 2006, Traish et al 2011, Koziol-White et al 2012. This protective activity of androgens against a bronchospasm revealed the same order of potency as that observed in the in vitro experiments described below (5b-DHT exhibited major potency than TES and 5a-DHT).…”
Section: Bronchospasm Prevention By Androgensmentioning
confidence: 72%
“…A study in hypogonadal men with type 2 diabetes has shown that testosterone replacement also improves glycemic control, although this study was non-blinded (14). By contrast, two studies replacing testosterone in men with type 2 diabetes and hypogonadism found little or no effect on glycemic control (15,16), but a more recent study analyzing the effects of testosterone administration to 24 hypogonadal men (10 treated with insulin) older than 30 years old with type 2 diabetes found that testosterone replacement therapy reduced insulin resistance (as measured by homeostatic model index) and improved glycemic control in hypogonadal men with type 2 diabetes (17). A recent study in newly diagnosed men showed convincingly that addition of testosterone to a regimen of diet and exercise produced significantly better results than diet and exercise on glycemic control and reversal of the metabolic syndrome (13).…”
Section: Administration Of Testosterone To Men With Diabetes Mellitusmentioning
confidence: 83%
“…Testosterone supplementation was able to reduce abdominal circumference and waist-hip ratio, and to improve insulin sensitivity and glycemic control in men with hypogonadism and type 2 diabetes mellitus (6,8,53,54). Testosterone replacement was also able to decrease the levels of pro-inflammatory cytokines (TNF-alpha, IL-1 and IL-6) produced by visceral adipocytes and associated with insulin resistance (27,55). Although the impact of these findings on an individual's cardiovascular risk have not been systematically investigated, concomitant improvements in glycemic control, insulin resistance, lipid profile and visceral adiposity probably represent an overall reduction in cardiovascular risk.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that insulin resistance, acting through signs mediated by the adipose tissue, including increased levels of leptin, would have a direct role in the regulation of gonadal function, thus decreasing the concentrations of testosterone (1,4,25,26). At the same time, pro-inflammatory cytokines, such as TNF alpha, IL-1 and IL-6, produced by visceral adipocytes, are also associated with insulin resistance (27,28). It was demonstrated that there is a strong correlation between insulin sensitivity and the function of Leydig's cell (29), but other studies have not confirmed such findings (23,30).…”
Section: Discussionmentioning
confidence: 99%